Skills for the Agricultural Industry: A Quantitative Analysis of Agricultural Educators’ Perceptions Regarding Their Personal Employability Skills - Norris, William; Garcia, Emily (Journal of Agricultural Systems, Technology, and Management, 2026)
Preparing students for career success has been a long-standing mission of agricultural education. Unfortunately, many employers claim that entry-level employees lack the employability skills necessary for success in the workforce. This disparity between the goal of agricultural education and feedback from employers has prompted the profession to reassess its strategy for promoting career success. Furthermore, if educators struggle with their personal employability skill development, it could diminish the impact on their students. Framed by the teacher career cycle model, we evaluated the self-perceived employability skills of agricultural educators in three states– Alabama, Georgia, and Florida. We distributed an electronic survey to N = 399 educators via email and asked them to rate their confidence level in a particular skill using a Likert scale. We received n = 78 responses from the educators. The results suggested that teachers felt confident in their employability skills; however, skills such as modifying systems, improving systems, and time management were among the areas in which they felt the least confident. Furthermore, the results indicated that early-career educators valued their employability skills lower than their middle- and late-career peers, suggesting that employability skills are developed over time as an educator’s career progresses, which aligns with the teacher career cycle model. We recommend providing professional development to teachers with strategies to manage their time more effectively and enhance their instructional systems.